Qualificação profissional de pessoas com deficiência para inserção no mercado de trabalho em Fortaleza - Silva, Grayceane Gomes da (2014)
The present coursework proposed to comprehend how is occurring the process of insertion of people with disability in the labour market in Fortaleza, such as, which the professional qualification that is offered them. It intended, more specifically, analyze the questions referents the insertion of people with disability in the capitalist’s labour market, how configure the actions of professional qualification before the competence’s and employability rhetoric, beside of the importance that these people give to the work and the professional qualification. The methodological trajectory to undertake this study consisted of bibliographic and documental research and field research with application of semi structured interview with participants of the Warehouse assistant’s course of a specialized institution in the attendance of people with disability convened to the Labor and Social Development Office of the Ceará State (STDS). The trajectory of the people with disability is marked by social inequality and by the seclusion in institutions that directed to remove them to the collective relationships. In the last twenty years the social movements, have brought conquests, among these the insertion of some policies in the social field. So, from of legislation that obliged the recruitment of people with disability, the companies have to receive these people considered unproductive, add to that, before the competence’s rhetoric, is necessary ensure professional qualifications spaces for these people. So, the professional education for this group is offered, principally, in institutions of specialized attendance. In Fortaleza the courses are offered by these places, as from of a capitalist logic of to offer a formation in short period. The investigated institution realizes attendance for professional qualification, routing for the labour market and follow-up in the first months in the companies. The interviews were realized with six people, being four men and two women, with hearing loss, mental handicap and blindness. The schooling profile is of late access to the teaching levels, whereat only two concluded the high school, the others were participating of Yong and Adult Education, being that one had gave up to dedicate to the job. The participation in professional courses is related to the possibility of get a job, but two participants cited the choice by course for to consider interesting and a new learning. The meaning of to have a job second the interviewees is related to the idea of be dignifying, in the meaning that become more importants to the society, above can support oneself and to contribute to the support of the relatives. In the that be relative to professional experiences all had, even if for means of stage, above reports of informal jobs, with low salaries and without work rights. As from of the analyses realized in the investigative field we have how conclusion that the job for these people have a centralize for the subsistence guaranty, such as, that the professional qualification whereof participate are seen how possibility of to conquest a space of job, even not being in the area whereof the course the realized. The conclusions of our field investigation, added to the documental analyses and to the literary study pertinent, take us to conclude that although the people with disability find an opportunity of social insertion in the labour force experience, receive specific professional capacitation, still find, how the others people of the worker class, jettisoned of a full social insertion, input the selves structural conditions of de capitalist system and of the form historical of prejudice and discrimination that these people suffered along the time.